Processing delays across disciplines. - Koh, Han Xiang. (2012)
Processing delay, with regards to academic journal submission, is the average time that elapses between the submission of a paper and the first editorial decision. It excludes desk rejection, which refers to those rejected directly by the editors or associate editors without being sent for peer review. This delay may often be frustratingly long for academics attempting to get their research published, especially for those seeking to establish their credentials for tenure and promotion. In this paper,we tested our hypothesis that there may be systematic differences in processing delays across different research disciplines.